CENOZOIC VOLCANISM OF PANCARDI: EVOLUTION AND GENESIS - Liashkevych, Z. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Alpine period of PANCARDI defined three main phases of magmatism: Mesozoic, Miocene and Pliocene-Pleistocene. The ultra-basic and basic intrusions had been complete by Late Mesozoic, in the Miocene there formed intermediate and acid volcanic rocks, while alkaline basalts – in the PliocenePleistocene. Acid volcanism (the rhyolite-dacite formation) preceded intermediate and basic volcanism (the andesite formation), which is confirmed by absolute dating. Miocene acid volcanic activity cannot be separated from andesite one. These two antidromic phases of continuing magmatic activity lasted for 10-15 Ma; their sequences have large volumes of intermediate and acid magmas with shallow magma foci in the continental crust. Destruction and degradation of the continental crust resulted in local weakened fault zones, which were channels for rapid intrusion and crystallization of high-temperature melts. The destruction was related to the extension and fragmentation of the continental crust into separate blocks, which was accompanied by volcanism and uplifting of high-temperature deep fluids. These conditions caused explosive volcanism in the first phase and subsequent hydrothermal-metasomatic alteration. Originally, melts arose in the granite layer, and were followed by posterior basaltic layer, which was confirmed by the composition of the trapped xenoliths. Early Miocene volcanism phase is explosive and areal-fractured; it is revealed in the trans-Carpathian and the Pannonian basins. There was formed a thick (up to 700-1000 m) volcanic layer of ignimbrites, rhyolitic tuffs, pumice-scoria flows (the rhyolite-dacite formation). These volcanites are characterized by pronounced spatial and temporal variations and linked to areal deep faults. Later, there were formed volcanic structures of Kremnica Mountains in Slovakia, Börzsöny, Mâtra, Bükk, and Tokaj Mecsek Mountains in Hungary; Vyhorlat-Huta volcanic ridge in Ukraine; Apuseni Mountains, and Călimani-Harghita in Romania. These are predominantly andesites (the andesite formation). Lava outbursts were calm, and formed stratovolcanoes, lava flows, and dykes. Intrusion of alkaline-basaltic melts took place during the Miocene volcanism. Alkaline-basaltic volcanism mostly occurred in the structures with thinned continental crust. According to the composition and age the andesite formation was interpreted to correspond to the Cenozoic alkaline magmatism of Western Europe and belong to intraplate magmatism of continents, in which mantle plume genesis predominates. Alkaline rocks of the final phase of volcanism haven't been found on the territory of Ukraine. Paleotectonic environment in the early Miocene suggests that entire PANCARDI was a stable area with continental crust. Ensialic magmas, antidromic sequences of volcanism, geochemical composition, and relation to deep structures provide a conclusion that there was evidence of post-collisional geo-dynamic volcanism rather than one of classic subduction.
Keywords: PANCARDI; tectonics; magmatism; subduc; continental crust; oceanic crust